Showstopper eaudiobook - Lovesey, Peter (Peter Diamond Mystery, 2022)
In the six years since the start of the hit British TV show Swift, its cast and crew have been plagued by misfortune, beginning with the star actress's pulling out of the show before it began. By now there have been multiple injuries by fall, fire, or drowning; two deaths; and two missing persons cases. The media quickly decides it's a curse, but who's to say there isn't a criminal conspiracy afoot? Now that the filming has moved to Bath, Peter Diamond, Chief of the Avon and Somerset Murder Squad, is on the case. While the investigation into one fatal accident is underway, a cameraman goes missing, challenging even the most credulous to wonder if he might have been the victim of foul play rather than a jinx. How can so many things go wrong on one set in such a short time? Complicating already complex matters is the fact that Diamond's boss is trying her best to get him out of her hair; he may be forced to retire if he can't solve the case. Will this be the end for Peter Diamond?